Genetic Linkage Map Construction and QTL Analysis of Two Interspecific Reproductive Isolation Traits in Sponge Gourd - Wu, Haibin; He, Xiaoli; Gong, Hao; Luo, Shaobo; Li, Mingzhu; Chen, Junqiu; Zhang, Changyuan; Yu, Ting; Huang, Wangping; Luo, Jianning (Frontiers in Plant Science, 2016)
The hybrids between Luffa acutangula (L.) Roxb. and L.cylindrica (L.) Roem. have strong heterosis effects. However, some reproductive isolation traits hindered their normal hybridization and fructification, which was mainly caused by the flowering time and hybrid pollen sterility. In order to study the genetic basis of two interspecific reproductive isolation traits, we constructed a genetic linkage map using an F2 population derived from a cross between S1174 [L. acutangula (L.) Roxb.] and 93075 [L. cylindrica (L.) Roem.]. The map spans 1436.12 CentiMorgans (cM), with an average of 8.11 cM among markers, and consists of 177 EST-SSR markers distributed in 14 linkage groups (LG) with an average of 102.58 cM per LG. Meanwhile, we conducted colinearity analysis between the sequences of EST-SSR markers and the genomic sequences of cucumber, melon and watermelon. On the basis of genetic linkage map, we conducted QTL mapping of two reproductive isolation traits in sponge gourd, which were the flowering time and hybrid male sterility. Two putative QTLs associated with flowering time (FT) were both detected on LG 1. The accumulated contribution of these two QTLs explained 38.07 % of the total phenotypic variance (PV), and each QTL explained 15.36 and 22.71% of the PV respectively. Four QTLs for pollen fertility (PF) were identified on LG 1 (qPF1.1 and qPF1.2), LG 3 (qPF3) and LG 7 (qPF7), respectively. The percentage of PF explained by these QTLs varied from 2.91 to 16.79 %, and all together the four QTLs accounted for 39.98 % of the total PV. Our newly developed EST-SSR markers and linkage map are very useful for gene mapping, comparative genomics and molecular marker-assisted breeding. These QTLs for interspecific reproductive isolation will also contribute to the cloning of genes relating to interspecific reproductive isolation and the utilization of interspecific heterosis in sponge gourd in further studies.